Pengembangan Media Lacer (Lagu Ceria) Berbantuan Model Think Pair Share untuk Meningkatkan Hasil Belajar Siswa Kelas IV Pada Pembelajaran Pendidikan Pancasila di SD Negeri Bringin 02 Kota Semarang - Fajar Ardina Manzilatul Rochmah; Novi Setyasto (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
The purpose of this study was to develop and test the feasibility, effectiveness, and practicality of the Lacer (Lagu Ceria) media assisted by the Think Pair Share model with the hope of improving student learning outcomes. This study falls under the category of research and development (R&D) using the Bord and Gall model. A total of 40 students from grades IV and V at SD Negeri Bringin 02 for the 2024/2025 academic year participated in this study. A small-scale pilot test was conducted with 12 students from grade V, while the large-scale trial involved 28 students from grade IV. Data was collected through various non-test techniques, such as interviews, observations, questionnaires, grade sheets, and documentation. Additionally, test techniques, including pre-tests and post-tests, were conducted. The validation results from subject matter experts, language experts, and media experts indicated that the Lacer media was deemed “highly suitable” with an average score of 81%, reflecting the media's suitability. The level of satisfaction, categorized as “very good,” was evident from the survey responses filled out by teachers and students, with scores of 91% from teachers and 88.5% from students, indicating the practicality of the media. The effectiveness of the Lacer media was proven by the t-test results, which showed a significance value of 0.001 (<0.05) and an N-gain test value of 0.58, which falls into the “moderate” category. The criteria for feasibility, practicality, and effectiveness in improving learning outcomes in Pancasila Education for fourth-grade students at SD Negeri Bringin 02 on the topic of the history of the formulation of Pancasila have been met by the Lacer media assisted by the Think Pair Share model.